Membaca Repertoir Okky Madasari dalam Novel Maryam: Kajian Respon Estetik Wolfgang Iser - Moch Zainul Arifin (ESTETIK : Jurnal Bahasa Indonesia, 2019)
Abstract: This paper tried to trace Okky Madasari’s repertoire in Maryam novel. Research analysis used Wolfgang Iser’s aesthetic response in his book The Act of Reading: A Theory of Aesthetic response (1987). The results showed that the accumulation of Okky's interview as a journalist about Ahmadiyya in Lombok had presented the Ahmadiyya socio-cultural problems in Lombok, and the old literary texts as background. Okky used social norms in the form of conflict of expulsion and burning of Ahmadiyya, while historical norms appear from year to year tragedies are displayed from 1999 to 2003. Cultural norms of Ahmadiyya must be married to fellow Ahmadis, and Ahmadis have their own mosques for their worship activities. The old literature that influenced it seemed to be Ronggeng Dukuh Paruk, Pulang novel, and Saksi Mata as well as the story of Maryam binti Imran. All of these elements build the meaning of the novel by Okky as a strategy to slip hopes, views, and criticisms of background reality to convey foreground that is intended to be addressed. Foreground that appears is Okky trying to reflect at the same time the contemplation of the tragedy for the tragedy that befell the Ahmadis in Lombok. So that the hope that appears is to voice justice, human rights and civilization better. Because Indonesian constitution becomes and protects every citizen's rights.Keywords: Repertoire, socio-cultural norms, history, old literature and foreground